Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
Inverse of a function
Ex 1.3, 2 Deleted for CBSE Board 2024 Exams
Ex 1.3, 3 (i) Important Deleted for CBSE Board 2024 Exams
Ex 1.3, 3 (ii) Deleted for CBSE Board 2024 Exams
Ex 1.3 , 4 Deleted for CBSE Board 2024 Exams
Ex 1.3, 5 (i) Deleted for CBSE Board 2024 Exams
Ex 1.3, 5 (ii) Important Deleted for CBSE Board 2024 Exams
Ex 1.3, 5 (iii) Important Deleted for CBSE Board 2024 Exams
Ex 1.3 , 6 Deleted for CBSE Board 2024 Exams
Ex 1.3 , 7 Deleted for CBSE Board 2024 Exams
Ex 1.3 , 8 Important Deleted for CBSE Board 2024 Exams
Ex 1.3 , 9 Important Deleted for CBSE Board 2024 Exams
Ex 1.3, 10 Important Deleted for CBSE Board 2024 Exams
Ex 1.3, 11 Deleted for CBSE Board 2024 Exams
Ex 1.3, 12 Deleted for CBSE Board 2024 Exams
Ex 1.3, 13 (MCQ) Important Deleted for CBSE Board 2024 Exams
Ex 1.3, 14 (MCQ) Important Deleted for CBSE Board 2024 Exams You are here
Inverse of a function
Last updated at May 29, 2023 by Teachoo
Ex 1.3, 14 Let f : R – {(−4)/3} → R be a function defined as f (x) = 4𝑥/(3𝑥 + 4) The inverse of f is map g: Range f → R – {(−4)/3}given by (A) g (y) = 3𝑦/(3−4𝑦) (B) g (y) = 4𝑦/(4−3𝑦) (C) g (y) = 4𝑦/(3−4𝑦) (D) g (y) = 3𝑦/(4−3𝑦) f(x) = 4𝑥/(3𝑥 + 4) Calculating inverse Take f(x) = y Hence, equation becomes y = 4𝑥/(3𝑥 + 4) y(3x + 4) = 4x 3xy + 4y = 4x 3xy – 4x = – 4y x(3y – 4) = – 4y x = (−4𝑦)/(3𝑦 − 4) x = (−4𝑦)/(−1(−3𝑦 + 4)) x = 4𝑦/((4 − 3𝑦)) So, inverse of f = 4𝑦/((4 − 3𝑦)) ∴ g(y) = 4𝑦/((4 − 3𝑦)) Hence, B is the correct answer